(untitled) (Вестник КазНУ. Серия Экономическая, 2016)
The article analyzes the main theoretical and methodological approaches to the study of the labor market in works of representatives of different economic schools, reveals the features of the existing concepts of the formation of the labor market, it is emphasized that, in general, they complement each other, marked by both continuity and inconsistency. Theoretical models with multiple sectors and segments and empirical analysis using different kinds of data are then reviewed. A brief concluding section addresses some priority research needs. The article discusses the various theories of the labor market: classical, Keynesian, neoclassical. The labor market is seen as a broad and a narrow sense.